Rhododendrol‐induced leukoderma update II: Pathophysiology, mechanisms, risk evaluation, and possible mechanism‐based treatments in comparison with vitiligo. Issue 7 (5th May 2021) - Inoue, Shintaro; Katayama, Ichiro; Suzuki, Tamio; Tanemura, Atsushi; Ito, Shosuke; Abe, Yuko; Sumikawa, Yasuyuki; Yoshikawa, Momoko; Suzuki, Kayoko; Yagami, Akiko; Masui, Yukiko; Ito, Akiko; et al.
Abstract: A small proportion of individuals utilizing cosmetics containing rhododendrol developed leukoderma with various pathological conditions, in some cases indistinguishable from vitiligo. In this review, we investigate and evaluate the major considerations for developing rhododendrol‐induced leukoderma based on data from original or review articles published in the literature to provide a wide range of information regarding the pathophysiology, mechanisms, risk evaluation, and possible mechanism‐based treatments. We compile and discuss the latest information, including data related to the cytotoxicity of rhododendrol, cytoprotective functions, and involvement of the immune system, and consider the possibility of novel treatments based on the differences between individual patients and on the mechanism underlying the onset of the condition. Understanding the pathophysiology of rhododendrol‐induced leukoderma helps not only elucidate the mechanisms of non‐segmental vitiligo onset and progression, but also suggests prevention and treatment.